1968
DOI: 10.1172/jci105734
|View full text |Cite
|
Sign up to set email alerts
|

Control of myocardial oxygen consumption: relative influence of contractile state and tension development

Abstract: A B S T R A C T Myocardial oxygen consumption was measured in 11 anesthetized, open-chest dogs in order to compare in the same heart the relative influence on oxygen usage of tension development and the contractile or inotropic state, as reflected in Vmax, the maximum velocity of shortening of the unloaded contractile elements. The isovolumetrically contracting left ventricle was studied with left ventricular volume, heart rate, and systemic perfusion rate controlled. Wall tension, contractile element velocity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
63
1
2

Year Published

1974
1974
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(72 citation statements)
references
References 42 publications
6
63
1
2
Order By: Relevance
“…When arterial pressure in dogs was increased to levels at which autoregulation of coronary blood flow was lost (138±2 mm Hg), however, coronary flow reserve was reduced because resting coronary blood flow increased more than hyperemic coronary blood flow.39 Hence, although the results of our study in humans were similar to those performed in animals with an arterial pressure in the zone of coronary autoregulation, elevation of arterial pressure beyond the bounds of autoregulation might reduce maximal coronary reserve. In an open-chest, open-pericardium, anesthetized dog preparation in which coronary autoregulation was abolished with vasodilation (carbochromen or adenosine), increased left ventricular preload produced by volume expansion was associated with a reduction in the ratio of endocardial to epicardial coronary blood flow.4142 Total diastolic left circumflex coronary blood flow was either decreased41 or did not change.42 When heart rate and systemic perfusion rate were controlled in anesthetized, open-chest dogs, however, increased left ventricular volume was associated with increased left ventricular wall tension and myocardial oxygen demand. 43 Coronary blood flow increased in response to elevated left ventricular preload. The effect of increased left ventricular preload on total coronary blood flow in the conscious animal has not been studied.…”
Section: Previous Studiesmentioning
confidence: 99%
“…When arterial pressure in dogs was increased to levels at which autoregulation of coronary blood flow was lost (138±2 mm Hg), however, coronary flow reserve was reduced because resting coronary blood flow increased more than hyperemic coronary blood flow.39 Hence, although the results of our study in humans were similar to those performed in animals with an arterial pressure in the zone of coronary autoregulation, elevation of arterial pressure beyond the bounds of autoregulation might reduce maximal coronary reserve. In an open-chest, open-pericardium, anesthetized dog preparation in which coronary autoregulation was abolished with vasodilation (carbochromen or adenosine), increased left ventricular preload produced by volume expansion was associated with a reduction in the ratio of endocardial to epicardial coronary blood flow.4142 Total diastolic left circumflex coronary blood flow was either decreased41 or did not change.42 When heart rate and systemic perfusion rate were controlled in anesthetized, open-chest dogs, however, increased left ventricular volume was associated with increased left ventricular wall tension and myocardial oxygen demand. 43 Coronary blood flow increased in response to elevated left ventricular preload. The effect of increased left ventricular preload on total coronary blood flow in the conscious animal has not been studied.…”
Section: Previous Studiesmentioning
confidence: 99%
“…The findings of a detrimental influence of hypothyroidism on evolving infarction are not consistent with the expected findings ofa beneficial effect based on the hypothesis that hypometabolism caused by reduced thyroid availability would favorably alter the balance between myocardial oxygen consumption and demand by reducing metabolic rate (30). In part, this may be explainable, since metabolic rate appears to be a minor determinant of oxygen use compared to the energy requirements due to intramyocardial tension, contractile state, and heart rate (31,32). It is well established that thyroid hormone has direct and indirect intracellular actions that regulate the rate of metabolism (33,34).…”
Section: Discussionmentioning
confidence: 75%
“…Previous studies in mature dogs have demonstrated that the major determinants of myocardial oxygen consumption in anesthetized mature dogs are contractility and wall stress, that external cardiac work and basal metabolism are quantitatively less important determinants, and that electrical activation accounts for less than 1 % of myocardial oxygen consumption (3,4,27,28,29). Parmley and Tyberg (30) has estimated that contractility and wall stress each account for 30-40% of total myocardial oxygen consumption in the basal state whereas external cardiac work and basal metabolism each may account for 10-20%.…”
Section: Discussionmentioning
confidence: 99%